The Information Content of Market Liquidity: An Empirical Analysis of Liquidity at the Oslo Stock Exchange? - Johannes A. Skjeltorp; Bernt Arne Ødegaard (Norges Bank, 2009)
We investigate the information content of aggregate stock market liquidity and ask whether it may be a useful realtime indicator, both for financial stress, and real economic activity in Norway. We describe the development in a set of liquidity proxies at the Oslo Stock Exchange (OSE) for the period 1980-2008, with particular focus on crisis period 2007 through 2008, showing how market liquidity and trading activity changed for the whole market as well as for individual industry sectors. We also evaluate the predictive power of market liquidity for economic growth both in-sample and out-of-sample.
hdl:11250/2497614
Keywords: G10; G20; 330; liquidity; business cycles; financial crisis; economic activity